Implementation Of Employee Performance Management In The Regional Secretariat Leader Administration Bureau Riau Islands Province - Aura Tazkiatun Mutmainnah; Satriadi Satriadi; Fakhrizka Andriman; Icha Hermana Putri; Raul Quraisy (International Journal of Economics and Management Research, 2024)
This research aims to determine the implementation of Employee Performance Management in the Administrative Bureau of the Regional Secretariat of the Riau Islands Province. This research uses qualitative methods by collecting data in the form of observations and interviews. Data analysis used used descriptive analysis and triangulation. The results of this research show that the planning and staffing section of the Leadership Administration Bureau has implemented performance management for employees in carrying out their work. The planning process can be seen from the preparation and determination of employee performance targets. In the implementation of performance, it has also been carried out in accordance with their respective main tasks and functions. Communication and coordination are effective in implementing activities so that results are obtained as expected.